Immunological mechanisms of exercise therapy in dyslipidemia - Krüger, Karsten; Tirekoglou, Paulos; Weyh, Christopher (Frontiers in Physiology, 2022)
Numerous studies demonstrated the strong link between dyslipidemia and the cardiovascular risk. Physical activity and exercise represent effective prevention and therapy strategies for dyslipidemia and at the same time counteract numerous comorbidities that often accompany the disease. The physiological mechanisms are manifold, and primary mechanisms might be an increased energy consumption and associated adaptations of the substrate metabolism. Recent studies showed that there are bidirectional interactions between dyslipidemia and the immune system. Thus, abnormal blood lipids may favor pro-inflammatory processes, and at the same time inflammatory processes may also promote dyslipidemia. Physical activity has been shown to affect numerous immunological processes and has primarily anti-inflammatory effects. These are manifested by altered leukocyte subtypes, cytokine patterns, stress protein expression, and by reducing hallmarks of immunosenescence. The aim of this review is to describe the effects of exercise on the treatment dyslipidemia and to discuss possible immunological mechanisms against the background of the current literature.